The theater artist as a political subject of Latin American integration (International Seven Journal of Multidisciplinary, 2024)
This article seeks to debate the possibility of having theater artists as political subjects of Latin American integration, through a comparative methodology, crossing the training scenarios of these professionals in Brazil and Argentina.